Study of Photocurrent Enhancement Dependence on Background Doping in Quantum Dot Solar Cells by Numerical Simulations - Cedola, Ariel Pablo (2014)
This paper presents a theoretical study about quantum dot solar cells by means of numerical simulations, considering different doping levels in the intrinsic region of the cells, with the aim of evaluating the effect on the device's power conversion efficiency. Results of simulations performed over GaAs solar cells with InAs quantum dots, based on two different fabrication processes, are reported. The donor doping density in the intrinsic region was ranged from 1013 to 1017 cm-3. It is shown that, for a doping level of 7×1015 cm-3, the contribution of larger sized quantum dots to the photocurrent is increased by 50%, a very promising result in the search for new designs with higher efficiencies.